The impact of scripture in early Christianity - Boeft, J. den.; Poll-van de Lisdonk, M. L. van (Vigiliae Christianae, Supplements, 1999)
One of the most conspicuous innovations of early Christianity within Greco-Roman culture is its reliance upon a collection of authoritative texts. The ultimate author of Scripture was thought to be God Himself, whose will could and should be sought and found in these holy writings. For this reason it is not surprising that very soon these texts not only became the object of careful attention and scholarly study, but also put their stamp on the various forms and manifestations of early Christian life, such as martyrdom, asceticism, liturgy, art, and literature. This multifarious influence of Scripture is the subject of The Impact of Scripture in Early Christianity . It contains fourteen contributions, predominantly in English, by Belgian and Dutch scholars which have been gathered in a thematically ordered collection.